The Effect of Learning Motivation on Writing Skills of Observation Results in The Covid 19 Pandemic - Mateus Purbo Cahyono; Teti Sobari (IKIP Siliwangi, 2022)
The study was conducted to determine the effect of learning motivation on the results of writing observational report text (laporan hasil observasi, or LHO) skills, especially during the pandemic. The researcher makes a hypothesis that there is a significant influence on learning motivation in writing LHO texts. This research method is descriptive quantitative. The research data were processed by using a statistical package of the social sciences (SPSS) and Microsoft Excel applications. The number of samples were 32 students of class X SMAK BPK PENABUR Singgasana. The instruments used are test and non-test. The test data is the result of learning to write LHO texts, while the non-test data is the response of students to the questionnaire on the motivation to learn Indonesian. The results of the Spearman Rank test, have a significance of 0.002 and have a correlation of 0.521, meaning that between learning motivation and learning outcomes of LHO text materials, there is a moderate level relationship. The direction of the relationship between variables is positive. It can be explained that high learning motivation will produce high learning scores as well. Teachers need to give enthusiasm and present interesting learning consistently so that the students can be more motivated and obtain good learning outcomes as well. ABSTRAK Penelitian dilakukan untuk mengetahui pengaruh motivasi belajar terhadap hasil keterampilan menulis teks laporan hasil observasi (LHO), khususnya di masa pandemi. Peneliti membuat hipotesis yaitu terdapat pengaruh yang signifikan antara motivasi belajar terhadap menulis teks LHO. Metode penelitian ini yaitu deskriptif kuantitatif. Pengolahan data penelitian menggunakan aplikasi statistical package of the social sciences (SPSS) dan microsoft excell. Jumlah sampel adalah 32 peserta didik kelas X SMAK BPK PENABUR Singgasana. Instrumen yang digunakan yaitu tes dan nontes. Data tes adalah nilai hasil belajar menulis teks LHO sedangkan data nontes merupakan respon dari peserta didik terhadap angket motivasi belajar Bahasa Indonesia. Hasil uji Rank Spearman, memiliki signifikansi 0,002 dan memiliki korelasi sebesar 0,521, artinya antara motivasi belajar dengan hasil belajar materi teks LHO terdapat hubungan dengan tingkat sedang. Arah hubungan antarvariabel, positif. Hal tersebut dapat dijelaskan bahwa motivasi belajar yang tinggi akan menghasilkan nilai belajar tinggi pula. Guru perlu selalu memberikan semangat dan menyajikan pembelajaran yang menarik supaya siswa termotivasi dan memperoleh hasil belajar yang baik.